Variabilidade da tendência do desempenho das firmas: uma análise multinível - Schechtman, Louise (2012)
Understanding the variability in performance among firms, to understand what leads above average performance and competitive adv antage are among the main issues in the field of strategy. The competitive advantage is a construct with difficult operation for its complex meaning that lead for many interpretations. However it is often pointed to as causing above - average performance. The variability of firm performance over time is also treated frequently, especially at firm and sector levels. However, most empirical work in the field of strategy only gives a dimension to this variability, studying it only in terms of its average. A se cond dimension, the trend of performance, was considered in this study, using multilevel models. How t he performance of a firm evolves over time allows then a different classification , in terms of competitive advantage , competitive disadvantage or parity. C ompared these results with those of average performance made clear the importance of analyzing the performance of two dimensions: the average and its trend.